2018
DOI: 10.1063/1.5049877
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field tribological behaviors of aluminum-alloy and steel

Abstract: This paper used aluminum-alloy-2A02 (paramagnetic) and High-Speed-Steel (HSS) W18Cr4V (ferromagnetic) as the research objects to study the effect of DC magnetic-field on the dry tribology performance adopting the mutual matching methods (aluminum-alloy pin to HSS ring and HSS pin to aluminum-alloy to HSS ring, respectively). The wear rate of aluminum-alloy ring coupled with HSS pin was larger than that of pin coupled with HSS ring, which indicated that the influence of contacted surface size and hardness of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Others studies 1442 reported that wear was increased or decreased by the magnetic field, depending on the rubbing material and on the experimental conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Others studies 1442 reported that wear was increased or decreased by the magnetic field, depending on the rubbing material and on the experimental conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Xi et al [17] attributed the improvements of the tribological properties to increased dislocation density and refined ferrite. Further studies have shown that the wear resistance of high-speed steel [18] mild steel [19], medium steel [20] and bearing steel [16] improved as a result of magnetic field treatment. By applying a magnetic field during testing, Wei et al [21] and Tharajak and Nicomrat [22] observed a decrease in the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%